Asuhan Keperawatan Pada NY. R Dengan Gangguan Sistem Integumen Post Operasi Debridement : Ulkus Diabetikum Di Ruang Kemuning RSUD Dr. Soeselo Kabupaten Tegal - Maulia Arfin Hani; Tati karyawati; Muhammad Silahudin (STIKes Ibnu Sina Ajibarang, 2023)
Diabetic ulcers are partial or total damage to the skin which can extend to the tissues under the skin, tendons, muscles, bones or joints that occur in someone who has diabetes mellitus. The symptoms of a diabetic wound, namely a person experiencing a change in the shape of the foot, decreased pain sensation, decreased function of the oil and sweat glands, are early signs of the appearance of a diabetic wound (Purnomo et al., 2020).